CLIMATE CHANGE PERCEPTION AMONG STAKEHOLDERS AND CLIMATE CHANGE ADAPTATION DESCRIPTION BASED ON LOCAL WISDOM IN GUNUNGKIDUL, INDONESIA - Sulistyawati, Sulistyawati; Hastuti, Siti Kurnia Widi; Harjo, Budhi (Bumi Lestari; Vol 17 No 1 (2017), 2017)
Adaptation is a process of adjustment with the climate change by reducing its risk level to human. Meanwhile, the stakeholder can be defined as people who have an interest in climate change, either the policy maker or the population. This research is aimed atidentifying the current climate change’s situation in Gunungkidul, Indonesia;assessing stakeholder perception regarding climate change, and capturing climate change adaptation in local level. The research was conducted qualitatively through FGD and workshop to take account of perception among stakeholders.Climate change’s situation in Gunungkidul was identified by the extremely fluctuating precipitationlevel in the last 10 years.On the basis ofrespondent’s testimony, we come to know  that season can no longer bepredicted by their local wisdom calendar. The majority of them defined climate change as changing of season from dry to rainy season and vice versa. There were several forms of adaptation strategy taken by diverse people in Gunungkidul, considering their occupation. A farmer chose the crop that survives in dry condition (need less of water). On the other hand, an entrepreneur adaptated to climate change bycreating an everlasting business that remained unaffectedby seasonality or climate change. Meanwhile, a breeder acclimtized themselvesby preserving fodder like silage for their livestock. Lastly, government employees stated that they were left untouched by climate change. From this research, we come to a pointthat Gunungkidul is experiencing climate change’s impact in many sectors. Despite the fact that Gunungkidul citizens have a relatively low level of understanding about climate change, it can be seen that they have an adaptation strategy to climate change based on their local wisdom. Thus, in order to strengthen their adaptation capacity, we definitely require the support from the policy maker and local authority.